Effect of machining parameters on turning process of Inconel 718 - Pinheiro, Cleverson; Kondo, Marcel Yuzo [UNESP]; Amaral, Simone Simões; Callisaya, Emanuele Schneider [UNESP]; De Souza, José Vitor Candido [UNESP]; De Sampaio Alves, Manoel Cléber [UNESP]; Ribeiro, Marcos Valério [UNESP] (Taylor & Francis, 2021)
Inconel 718 superalloys are known materials with high applicability to components that demand exceptional chemical and mechanical properties at higher working temperatures combined with excellent surface finish requirements. However, due to the lack of in-depth knowledge regarding its machining process, the material is considered a difficult-to-machine material. Therefore, to improve the machining process of the Inconel 718 superalloy, by finding the optimal processing conditions, it was necessary to analyze the influence of the cutting parameters on the workpiece surface quality. In this work, the evaluation of quality indicators was made through the influence analysis of cutting speed, feed, tool, and lubrication parameters. The surface roughness (Ra, Rt), consumed power, vibration, and tool wear indicators were evaluated by following a Taguchi experimental design. To perform the machining process, the tool CNMG120408-M1 coating TS2500 with minimum quantity of lubricant was used. Results have proven that feed rate adjusted to 0.10 mm/rev and the cutting speed of 70 m/min provided the optimal processing results. It was observed that the feed increase led to an increase of all indicators. Consumed power denoted high sensibility concerning the machining parameters, suggesting its potential use in tool wear prediction studies applied for the Inconel 718 machining.
Keywords: machining; Measurements; MQL; nickel; parameters; power; roughness; superalloys; Taguchi; turning; wear